2011
DOI: 10.1590/s0100-06832011000200015
|View full text |Cite
|
Sign up to set email alerts
|

Substâncias húmicas e suas interações com Fe e Al em Latossolo subtropical sob diferentes sistemas de manejo de pastagem

Abstract: RESUMOGonçalves 7712, CEP 91540-000 Porto Alegre (RS).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
7
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 33 publications
(25 reference statements)
2
7
0
1
Order By: Relevance
“…For the Al, a contrary trend was observed, since this ion is more associated with the FA fraction, even after extract purification with DAX-8 resin (Table 5). Similar results were observed by Sarante et al (2011), who verified a higher molar Al/Fe ratio in FA than in HA, confirming the higher affinity of Al for the FA organic ligands. The higher affinity of Fe and Al for these humic fractions may be due to differences in their chemical composition.…”
Section: Iron and Al Contents Associated With Som Chemical Fractionssupporting
confidence: 88%
See 2 more Smart Citations
“…For the Al, a contrary trend was observed, since this ion is more associated with the FA fraction, even after extract purification with DAX-8 resin (Table 5). Similar results were observed by Sarante et al (2011), who verified a higher molar Al/Fe ratio in FA than in HA, confirming the higher affinity of Al for the FA organic ligands. The higher affinity of Fe and Al for these humic fractions may be due to differences in their chemical composition.…”
Section: Iron and Al Contents Associated With Som Chemical Fractionssupporting
confidence: 88%
“…The same trend was observed for Al, which showed mean values of 11,088 mg kg -1 in HSs, 234 mg kg -1 in HCl extract, and 53 mg kg -1 in water extract (Table 5). Both the Fe and Al contents observed in the SOM fractions were generally higher than those observed in humic and non-hydromorphic soils of altitude in the state of Rio Grande do Sul (Sarante et al, 2011).…”
Section: Iron and Al Contents Associated With Som Chemical Fractionsmentioning
confidence: 60%
See 1 more Smart Citation
“…Solo, 38:923-933, 2014 management (Fontana et al, 2006). Several studies have reported the influence of agricultural management systems on the humic fractions (Barreto et al, 2008;Portugal et al, 2008;Santana et al, 2011). The use of no-tillage, for example, preserves organic C in all humic fractions (Rosa et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Essa fração orgânica, composta principalmente por compostos bioquimicamente lábeis e de origem microbiana e exsudação radicular (SANTANA et al, 2011), aumentou sua proporção (CHCl/COT) gradualmente em profundidade em todos os ambientes, sugerindo um processo de migração (Tabela 2). Entre os ambientes, a relação CHCl/COT aumentou na camada 0,0-0,05m dos ambientes afetados pela ação antrópica (FP, LA e CNq).…”
unclassified